Food Waste and Loss in the Food Service Industry of Tanzania: Learning from the Value Addition Chain - Felichesmi Selestini Lyakurwa (International Journal on Food, Agriculture and Natural Resources, 2023)
Food waste and loss is a current issue of global concern due to its significant effect on the country’s food security. Despite the importance of food service industry on the control of food waste, yet the magnitude of waste and food loss in each stage of the value chain is not clear. This study intended to explore the extent of food loss and waste, and dominant factors for the food loss and waste along the value chain. A well-structured questionnaires and interview guide questions were used to collect primary data from customers (n = 80), and working staff at restaurants/canteen n = 20). Quantitative and qualitative methods of data analysis were employed in the analysis whereby Structural Equation Modeling technique through Confirmatory Factor Analysis was employed to establish the dominant factors for the food loss and waste at each stage in the value chain. The findings revealed that the main kinds of food loss and wastes generated at different stages includes beans, rice, vegetables, food remains e.g., ugali and left outs, meat, fish, bananas and tomato such that rice and beans losses are dominant i.e., rated at 73%. Also, more food loss and waste occur at the production stage mainly during harvesting. The main causes of food loss and waste in the value chain are mostly lack of post-harvest and food preservation technology, customers’ and working staff ignorance, poor hygienic storage and preservation facilities. With this positive foundation, the study recommends future research to determine customers’ perceptions and behavioral patterns regarding food loss and waste along the value chain.